Microstructural insights into the lime mortars mixed with sticky rice sol–gel or water: A comparative study. (30th October 2016) - Yang, Rongwei; Zhang, Zhiling; Xie, Meijie; Li, Kefei
Highlights: Sticky rice slurry refines pore structure and increases strength of lime mortar. Fractal dimension of pore structure is decreased by adding rice slurry. Sticky rice slurry forms more compact inter-granular microstructure. Abstract: This paper is dedicated to studying the effect of sticky rice sol–gel on the microstructure (including pore structure and texture) and properties of lime mortar. Uniaxial compressive strength tests, scanning electron microscopy (SEM), and mercury intrusion porosimetry (MIP) were utilized to investigate the macroscopic behaviors and microstructure, respectively. Based on the MIP data, a surface fractal dimension analysis is performed to study the impact of sticky rice sol–gel on pore structure. The addition of sticky rice sol–gel is demonstrated to improve the uniaxial compressive strength of lime mortar. The SEM, MIP and surface fractal dimension analysis results show that the addition of sticky rice sol–gel facilitates the formation of compact texture, fine pore structure and elevates the bonding strength of the lime mortar. A microstructrual mechanism is proposed to explain how properties of the lime mortar are affected by the addition of sticky rice sol–gel.